Functional polarization of macrophages of rats with progesterone-induced obesity treated with melanin from the Antarctic yeast Nadsoniella nigra - Konopelnuk, V. I.; Kompanets, I. V.; Svyatetska, V. M.; Molozhavaya, O. S.; Ostapchenko , L. I. (Regulatory Mechanisms in Biosystems, 2019)
Progesterone-induced obesity develops in women who use this drug for contraception and the menopause treatment, though its mechanisms remain poorly understood. We studied functional M1 and M2 polarizations of the abdominal cavity macrophages of rats with progesterone induced obesity during 28 days of administration. The effect of melanin from the Antarctic yeast Nadsoniella nigra (Chaetothyriales, Herpotrichiellaceae, Nadsoniella Issatsch, 1914) was investigated. The NO level was determined by the accumulation of nitrites, ROS level was estimated by the NBT-test, arginase activity was assayed by the reaction of L-arginine hydrolysis. The body weights of rats administrated progesterone increased by 27% and continued to increase one month after withdrawal of progesterone (55% higher than control). Melanin prevents the weight gain when administered during one month after progesterone withdrawal. The NO production by peritoneal macrophages of obese animals intensified by 31% indicating their polarization towards pro-inflammatory M1 type. Production of ROS did not change. A 14% increase in arginase activity was observed, indicating the inhibition of M2 (anti-inflammatory) polarization. In the progesterone withdrawal group all these rates significantly decreased, indicating a reduction in the functional activity of peritoneal macrophages’. Melanin decreased the NO and ROS production by 60% and 18% respectively in comparison with the progesterone group and unexpectedly reduced arginase activity. Our data provide evidence of the spread of inflammation in response to progesterone-induced obesity. Peritoneal macrophages are involved in the inflammation in obesity, undergoing polarization towards the pro-inflammatory phenotype. The long-term consequences of such inflammation include the continuation of weight gain and likely the development of systemic inflammation associated with the exhaustion of the functional capacity of peritoneal cavity macrophages. Melanin has an anti-obesity effect and exhibits anti-inflammatory properties preventing progesterone-induced weight gain and macrophage M1 polarization. This requires detailed elucidation and can be valuable in designing countermeasures to prevent obesity outcomes.